Intracerebral Hemorrhage Score as a Prognosis Prediction of Spontaneous Intracerebral Hemorrhage at RSI Surabaya Jemursari - Dyah Yuniati; Shobihatus Syifak; Prima Ardiansah Putra; Vena Saskia Prima Saffanah (AKSONA, 2023)
Highlight: Spontaneous intracerebral hemorrhage, or hemorrhagic stroke, is one of the leading causes of mortality and disability in Indonesia. The intracerebral hemorrhage (ICH) score is a widely used predictive tool for the prognosis of death 30 days after spontaneous intracerebral hemorrhage, but the intracerebral hemorrhage-grading scale (ICH-GS) score has a more specific interval to assess prognosis prediction after intracerebral. The higher the total score, the more likely it is to have a poor outcome. The results of this study indicate that patients with a high total score did not always die.   ABSTRACT Introduction: Spontaneous intracerebral hemorrhage, or hemorrhagic stroke, is one of the leading causes of mortality and disability in Indonesia. Objective: The intracerebral hemorrhage (ICH) score is a widely used predictive tool for the prognosis of death 30 days after spontaneous intracerebral hemorrhage, but the intracerebral hemorrhage-grading scale (ICH-GS) score has a more specific interval to assess prognosis prediction after intracerebral hemorrhage. Methods: The type of research used was observational-retrospective research. The population included all patients with spontaneous intracerebral hemorrhage hospitalized at RSI Jemursari Surabaya in 2017–2019. Results: The results revealed that there were 110 spontaneous intracerebral hemorrhage patients with complete data in medical e-records during 2017–2019; 65.5% (72 patients) were male and 34.5% (38 patients) were female. The data showed that 20% (22 patients) had an ICH-GS score of 8 and 0.9% (1 patient) had an ICH-GS score of 12. Conclusion: The higher the total score, the more likely it is to have a poor outcome. The results of this study indicate that patients with a high total score did not always die.